Electrical efficiency of the heat pipe cooled photovoltaic systems - Amer Hussein Albozidi (Aljameai, 1970)
Abstract:          The solar PV modules framework has been executed into the sun oriented heat vitality utilization framework, yielding made strides sun oriented vitality use effectiveness. The two key objectives of the solar framework plan utilizing heat pipe cooling advances were the heat stream of the PV module and the exchange execution heating. Heat units (ε-NTU) approach will be utilized with regard to mechanical analysis and computation of the particular thermoelectric heat pipe efficiency. As the emerged coolant degree and plate degree, the heat and electrical yield of the unit, and the researches illustrates that the whole of distinction within the electrical and heat productivity of the framework is 6.99 percent, 7.46 percent, and 63.2 percent, respectively This article gives a promising approach to considering the proficiency of heat exchange utilizing heat pipes, which can be utilized to degree and treat the impact of factors influencing the system's success.